Concrete Corrosion Mechanism and Durability Design of Municipal Sewerage. Issue 1 (February 2021) - Zhang, Wanlai; Zhao, Chunyang; Zhang, Chunmei; Guo, Chunlei
Abstract: In recent years, with the rapid development of urbanization, urban sewage pipe has become an important infrastructure, which plays a significant role in urban ecological security and social production development. Based on the investigation and analysis of concrete corrosion of sewage pipe in a certain city, the indoor simulated corrosion test is carried out, and the durability design method of sewage pipe concrete is put forward. Research findings show that the main cause of concrete corrosion failure in sewage pipe is sulfate erosion, and the modification of pipe concrete by mineral admixture and polypropylene fiber can effectively improve the durability of pipe concrete in sewage corrosion environment.